Ultrasound-guided anterior neck soft tissue measurements in the prediction of difficult laryngoscopy: A prospective observational study - Kafle, Swairita; Prahlad Adhikari,; Ravi Sulabh Yadav,; Sabin Bhandari, (Journal of Gandaki Medical College-Nepal, 2026)
Introduction: Difficult laryngoscopy remains a significant challenge in anesthetic practice, occurring in 1.5% to 13% of cases. Point-of-care ultrasound has emerged as a potential tool for predicting difficult laryngoscopy. This study evaluated the utility of ultrasound measurements of anterior neck soft tissue thickness in predicting difficult laryngoscopy.Methods: This prospective observational study included 140 adult patients (ASA I-II) undergoing elective surgery requiring general anesthesia and endotracheal intubation. Modified Mallampati Grade, thyromental distance, inter-incisor gap, neck circumference, and body mass index were recorded and ultrasound measurements of distance from skin to hyoid bone (DSHB), skin to epiglottis midway between hyoid and thyroid cartilage (DSEM), and skin to anterior commissure (DSAC) were obtained preoperatively. Laryngoscopy view was graded using the Modified Cormack-Lehane classification. Receiver operating characteristic curve analysis was performed to determine the diagnostic accuracy of each parameter.Results: Out of 140 patients, 33(23.6%) had difficult laryngoscopy. DSEM demonstrated superior predictive performance with an area under the curve (AUC) of 0.867, sensitivity of 90.9%, and specificity of 79.4% at a cutoff of 1.69 cm (p